Adventitious root culture dyeing and optimisation of dyeing parameters using roots of Gynochthodes umbellata (L.) Razafim and B. Bremer : nil - AS, Vidhya; V R, Sumitha; Gangaprasad, Gangaprasad (Plant Science Today, 2024)
This study offers a new source of natural dye. Taguchi's design of experiments was used to statistically and optimize the dyeing parameters of different fabrics. The results varied with different fabrics and the optimum conditions for cotton were found to be ultrasonication for 5 min, a material-to-liquor ratio of 10 mL dye to 100 mL water, a temperature of 60 ºC, and a pH of 8. For linen, the optimum values were ultra-sonication for 15 min, 15 mL dye to 100 mL water, pH of 8, and temperature of 80 ºC. Optimum combinations for silk were a temperature of 80 ºC, the material-to-liquor ratio of 20 mL of dye extract to 100 mL water, pH of 8, and ultrasonication for 15 min. The results indicated the commercial viability of dyeing fabrics using this procedure.